Targeting the Epidermal Growth Factor Receptor Can Counteract the Inhibition of Natural Killer Cell Function Exerted by Colorectal Tumor-Associated Fibroblasts - Costa, Delfina; Venè, Roberta; Benelli, Roberto; Romairone, Emanuele; Scabini, Stefano; Catellani, Silvia; Rebesco, Barbara; Mastracci, Luca; Grillo, Federica; Minghelli, Simona; Loiacono, Fabrizio; Zocchi, Maria Raffaella; et al. (Frontiers in Immunology, 2018)
Mesenchymal stromal cells (MSC) present in the tumor microenvironment (usually named tumor-associated fibroblasts, TAF) can exert immunosuppressive effects on T and natural killer (NK) lymphocytes, favouring tumor immune escape. We have analyzed this mechanism in colorectal carcinoma (CRC) and found that co-culture of NK cells with TAF can prevent the IL2-mediated NKG2D upregulation. This leads to the impairment of NKG2D-mediated recognition of CRC cells, sparing the NK cell activation through DNAM1 or FcγRIIIA (CD16). In situ, TAF express detectable levels of epidermal growth factor receptor (EGFR); thus, the therapeutic anti-EGFR humanized antibody cetuximab can trigger the antibody dependent cellular cytotoxicity of TAF, through the engagement of FcγRIIIA on NK cells. Importantly, in the tumor we found a lymphoid infiltrate containing NKp46+CD3- NK cells, enriched in CD16+ cells. This population, sorted and cultured with IL2, could be triggered via CD16 and via NKG2D. Of note, ex-vivo NKp46+CD3- cells were able to kill autologous TAF; in vivo, this might represent a control mechanism to reduce TAF-mediated regulatory effect on NK cell function. Altogether, these findings suggest that MSC from the neoplastic mucosa (TAF) of CRC patients can down-regulate the immune cell recognition of CRC tumor cells. This immunosuppression can be relieved by the anti-EGFR antibody used in CRC immunotherapy.